Outcome of Patients With Recurrent Osteosarcoma Enrolled in Seven Phase II Trials Through Children's Cancer Group, Pediatric Oncology Group, and Children's Oncology Group: Learning From the Past to Move Forward - Joanne P. Lagmay; Mark Krailo; Ha Dang; AeRang Kim; Douglas S. Hawkins; Orren Beaty; Brigitte C. Widemann; Theodore Zwerdling; Lisa Bomgaars; Anne‐Marie Langevin; Holcombe E. Grier; Brenda J. Weigel; et al. (2016)
The use of radiographic response as the primary end point in phase II osteosarcoma trials may limit optimal detection of treatment response because of the calcified tumor matrix. We performed this study to determine if time to progression could be used as an end point for subsequent studies.We performed a retrospective analysis of outcome for patients with recurrent/refractory osteosarcoma enrolled in one of seven phase II trials conducted by the Children's Oncology Group and predecessor groups from 1997 to 2007. All trials used RECIST or WHO radiographic response criteria and the primary end point of response rate. The following potential prognostic factors-age, trial, number of prior chemotherapy regimens, sex, and race/ethnicity-were evaluated for their impact on event-free survival (EFS). We used data from a phase II study (AOST0221) of patients with osteosarcoma who were given inhaled granulocyte-macrophage colony-stimulating factor with first pulmonary recurrence who had an EFS as well as biologic end point to determine the historical disease control rate for patients with fully resected disease.In each included trial, the drugs tested were determined to be inactive on the basis of radiographic response rates. The EFS for 96 patients with osteosarcoma and measurable disease was 12% at 4 months (95% CI, 6% to 19%). There was no significant difference in EFS across trials according to number of prior treatment regimens or patient age, sex, and ethnicity. The 12-month EFS for the 42 evaluable patients enrolled in AOST0221 was 20% (95% CI, 10% to 34%).The EFS was uniformly poor for children with recurrent/refractory osteosarcoma in these single-arm phase II trials. We have now constructed baseline EFS outcomes that can be used as a comparison for future phase II trials for recurrent osteosarcoma.